Perancangan Sistem Informasi Akuntansi atas Penjualan Tunai pada CV. 99 Jaya - Tasya Putri Nuria; Eka Jumarni Fithri; Anggeraini Oktarida (Pusat Riset dan Inovasi Nasional, 2023)
The sales accounting information system is one of the company's main activities to generate company profits. So this process requires good process management to produce maximum profits. CV. 99 Jaya is a company engaged in the trading business which sells various types of sea fish. The data collection technique used is by survey in the form of interviews and documentation. From the information obtained by the author, a problem was found, namely that the company had not used computer tools in recording sales, so in this case, errors often occurred in the process of calculating sales transaction recaps so that it took quite a long time in the recording process to produce a profit and loss report. Based on these problems, the author designed a sales accounting information system that produces output in the form of a profit and loss report which is expected to overcome the problems that occur in the company. This discussion produces a sales accounting information system design that is tailored to the needs and agreement with the company.